Social jet lag is associated with core symptoms in 2-3-year-old children with autism spectrum disorders - Hongyu Chen; Ting Yang; Jie Chen; Yuan Ding; Yuan Ding; Xueli Xiang; Qiuhong Wei; Qiuhong Mou; Binlin Yuan; Binyue Hu; Danyang Zhang; Dan Ai; et al. (Frontiers in Psychiatry)
BackgroundSocial jet lag (SJL) is a form of circadian rhythm misalignment caused by the mismatch between social schedules and biological clocks, which is associated with cognition, behavior, and emotion in children. However, social jet lag among children with autism spectrum disorders (ASD) and its impacts are unknown.MethodsThis cross-sectional study recruited 2-7-year-old children with ASD from special education institutions and outpatient clinics. The Children’s Sleep Habits Questionnaire (CSHQ) assessed children’s sleep. SJL was calculated as |weekend sleep midpoint - weekday sleep midpoint|. Sleep adequacy was determined based on the National Sleep Foundation’s recommendations. Core symptoms were evaluated using the Childhood Autism Rating Scale (CARS), Social Responsiveness Scale (SRS), and Autism Behavior Checklist (ABC). Developmental level was assessed using the Gesell Developmental Scale.Results1) The prevalence of sleep problems was 49.8% and the mean CSHQ total score was 48.04 in ASD. There are significant differences in sleep patterns between weekends and weekdays, characterized by later bedtimes, delayed wake-up times, increased total sleep duration, and reduced prevalence of sleep deficiency during weekends. 2) The 2-3-year-old group had the highest rates of sleep insufficiency (80.77% on weekdays; 82.17% on weekends). There were no significant differences in sleep duration across different age groups, with the median sleep duration ranging from 9.5 to 10 hours. 3) Median SJL in each age group was 0.25 h (2–3 years), 0.5 h (3–4 years), 0.42 h (4–5 years), and 0.5 h (≥5 years), respectively. In children aged 2–3 years, SJL was significantly positively correlated with core symptoms 4) SJL was observed to be weakly associated with developmental level of personal-social only in the ≥ 3-year-old group (r = 0.100, P = 0.042).ConclusionOur study found for the first time a correlation between SJL and core symptoms in 2-3-year-old children with ASD. This finding suggests that SJL may have a potentially negative impact on core symptoms in ASD. Therefore, it is crucial to emphasize the importance of regular routines for ASD, especially in younger children.